Ending the HIV epidemic in the USA: an economic modelling study in six cities. Issue 7 (July 2020) - Nosyk, Bohdan; Zang, Xiao; Krebs, Emanuel; Enns, Benjamin; Min, Jeong E; Behrends, Czarina N; del Rio, Carlos; Dombrowski, Julia C; Feaster, Daniel J; Golden, Matthew; Marshall, Brandon D L; Mehta, Shruti H; et al.
Summary: Background: The HIV epidemic in the USA is a collection of diverse local microepidemics. We aimed to identify optimal combination implementation strategies of evidence-based interventions to reach 90% reduction of incidence in 10 years, in six US cities that comprise 24·1% of people living with HIV in the USA. Methods: In this economic modelling study, we used a dynamic HIV transmission model calibrated with the best available evidence on epidemiological and structural conditions for six US cities: Atlanta (GA), Baltimore (MD), Los Angeles (CA), Miami (FL), New York City (NY), and Seattle (WA). We assessed 23 040 combinations of 16 evidence-based interventions (ie, HIV prevention, testing, treatment, engagement, and re-engagement) to identify combination strategies providing the greatest health benefit while remaining cost-effective. Main outcomes included averted HIV infections, quality-adjusted life-years (QALYs), total cost (in 2018 US), and incremental cost-effectiveness ratio (ICER; from the health-care sector perspective, 3% annual discount rate). Interventions were implemented at previously documented and ideal (90% coverage or adoption) scale-up, and sustained from 2020 to 2030, with outcomes evaluated until 2040. Findings: Optimal combination strategies providing health benefit and cost-effectiveness contained between nine (Seattle) and 13 (Miami) individual interventions. If implemented at previously documented scale-up, these strategies could reduce incidence by between 30·7% (95% credible interval 19·1–43·7; Seattle) and 50·1% (41·5–58·0; New York City) by 2030, at ICERs ranging from cost-saving in Atlanta, Baltimore, and Miami, to 95 416 per QALY in Seattle. Incidence reductions reached between 39·5% (26·3–53·8) in Seattle and 83·6% (70·8–87·0) in Baltimore at ideal implementation. Total costs of implementing strategies across the cities at previously documented scale-up reached 559 million per year in 2024; however, costs were offset by long-term reductions in new infections and delayed disease progression, with Atlanta, Baltimore, and Miami projecting cost savings over the 20 year study period. Interpretation: Evidence-based interventions can deliver substantial public health and economic value; however, complementary strategies to overcome social and structural barriers to HIV care will be required to reach national targets of the ending the HIV epidemic initiative by 2030. Funding: National Institutes of Health.